2016
DOI: 10.1111/jav.00700
|View full text |Cite
|
Sign up to set email alerts
|

Nest as an extended phenotype signal of female quality in the great reed warbler

Abstract: Extended phenotypes with signalling function are mostly restricted to animal taxa that use construction behaviour during courtship displays. However, they can be used also as post‐mating signals of mate quality, allowing individuals to obtain reliable information about their partners. Nest size may have such a signalling function and a lot of indirect evidence supports this view. However, direct evidence based on an experimental approach is still widely missing. Here we test the role of nest size in post‐matin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 59 publications
(84 reference statements)
0
17
1
Order By: Relevance
“…Nest decoration has been proposed as a sexually selected ‘honest signal’, or extended female phenotype, in some species such as the Great Reed Warbler Acrocephalus arundinaceus (Jelínek et al . ) but our results could not confirm this for our alpine population of Horned Larks, despite the apparent energetic costs of constructing nest decoration. Therefore, nest decoration behaviour is either not as energetically costly as it may appear, and thus is not linked to individual female quality, or we were unable to explain some of the residual variation in nest decoration size without explicit measurements of female condition or reproductive investment.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Nest decoration has been proposed as a sexually selected ‘honest signal’, or extended female phenotype, in some species such as the Great Reed Warbler Acrocephalus arundinaceus (Jelínek et al . ) but our results could not confirm this for our alpine population of Horned Larks, despite the apparent energetic costs of constructing nest decoration. Therefore, nest decoration behaviour is either not as energetically costly as it may appear, and thus is not linked to individual female quality, or we were unable to explain some of the residual variation in nest decoration size without explicit measurements of female condition or reproductive investment.…”
Section: Discussioncontrasting
confidence: 91%
“…1). Nest decorations have been observed in other passerine and non-passerine species but this trait is often displayed by the male and/or has a variety of ecological functions such as thermoregulation (Yosef & Afik 1999), signalling individual quality (Soler et al 1996, Jel ınek et al 2016 and interactions among conspecifics (Sergio et al 2011). Proposed drivers of this decoration behaviour for species in the Lark family (Alaudidae) include camouflage and thermoregulation (Cannings & Threlfall 1981, Fijen et al 2015 but the functional significance has not been established for Horned Larks.…”
mentioning
confidence: 99%
“…However, because this color signal is expressed in the eggs, the female's potential mortality risk due to the expressed sexual signal should be lower than in species with ornamented females, from the perspective of detection by predators. Nest size has also been used as a form of signal by males in the Great Reed Warbler (Acrocephalus arundinaceus) (Jelínek et al 2016), and has been indicated to have no effect on nest predation or parasitism in the field (Jelínek et al 2015). Moreover, female feather carrying in the nest has also recently been proposed to affect male investment (Garcia-Navas et al 2015).…”
Section: The Importance Of a Less Costly Signalmentioning
confidence: 99%
“…This behavior, which normally happens in females, has received abundant empirical support in different taxa (Sheldon 2000), but males can also adjust their parental care investment according to their mates' ornamental attractiveness (e.g., Burley 1988;Roulin 1999;Matessi et al 2009;Mahr et al 2012). Moreover, a number of empirical studies have suggested that some signals expressed after pairing are intended to induce higher investment of paternal care from the male parent; such signals include avian eggshell pigmentations (e.g., Moreno et al 2005;Soler et al 2005;Hanley and Doucet 2009;English and Montgomerie 2011), nest size (Jelínek et al 2016), and female feather carrying in the nest (Garcia-Navas et al 2015). These findings raise the question of why postpairing male mate choice would evolve.…”
mentioning
confidence: 99%
“…In this context, nest attributes may provide honest signals of direct benefits, for example, through improved parental care (De Neve, Soler, Soler, & Perez‐Contreras, ), and indirect benefits, for example, through elevated immune function (Soler, Martin‐Vivaldi, Haussy, & Moller, ). In birds, nests often contribute to postmating sexual selection, for example, by stimulating males to invest more feeding effort when females had invested more into nest building (Jelinek, Pozgayova, Honza, & Prochazka, ).…”
Section: Introductionmentioning
confidence: 99%